Altitude training causes haematological fluctuations with relevance for the Athlete Biological Passport - Bonne, T. C.; Lundby, C.; Lundby, A. K.; Sander, M.; Bejder, J.; Baastrup Nordsborg, N. (Drug Testing and Analysis, 2014)
The impact of altitude training on haematological parameters and the Athlete Biological Passport (ABP) was evaluated in international-level elite athletes. One group of swimmers lived high and trained high (LHTH, n = 10) for three to four weeks at 2130 m or higher whereas a control group (n = 10) completed a three-week training camp at sea-level. Haematological parameters were determined weekly three times before and four times after the training camps. ABP thresholds for haemoglobin concentration ([Hb]), reticulocyte percentage (RET%), OFF score and the abnormal blood profile score (ABPS) were calculated using the Bayesian model. After altitude training, six swimmers exceeded the 99% ABP thresholds: two swimmers exceeded the OFF score thresholds at day +7; one swimmer exceeded the OFF score threshold at day +28; one swimmer exceeded the threshold for RET% at day +14; and one swimmer surpassed the ABPS threshold at day +14. In the control group, no values exceeded the individual ABP reference range. In conclusion, LHTH induces haematological changes in Olympic-level elite athletes which can exceed the individually generated references in the ABP. Training at altitude should be considered a confounding factor for ABP interpretation for up to four weeks after altitude exposure but does not consistently cause abnormal values in the ABP. Altitude training causes haematological fluctuations with relevance for the Athlete Biological Passport.